Um modelo integrativo dos efeitos das intera????es na lealdade do aluno: educa????o a dist??ncia versus educa????o presencial em cursos de administra????o - Nascimento, Carlos Alberto Xavier do (2019)
In Brazilian Higher Education, the proportion of students who have been evaded is high, especially in Distance Learning (DL), a phenomenon that is at the heart of this PhD Thesis. Information and Communication Technologies expand the offer of education and favor social inclusion, but the DL physically distances the student from the institution. The greater autonomy of this 'new student' of DL is accompanied by a reduction in the actual interaction of Face-to-face Teaching, which can trigger a sense of isolation (apart from the spatial, natural in the modality). In this context, the Dissertation investigated effects on the DL???s Student Loyalty with a view to an Integrative Model, which has Interaction, Value Co-creation, Value Co-destruction, Perceived Value, Satisfaction and Brand Image as antecedents. In the Main Model, 11 hypotheses were enunciated with logical foundations and support in the literature. Another hypothesis of mediation is linked to a Rival Model. In order to test them, a descriptive empirical research was carried out, a survey with students (682 of the DL, 707 of Classroom Teaching) and analysis by Modeling of Structural Equations. The Main Model was valid in DL and in Classroom Teaching. In Classroom Teaching, all hypotheses were supported by the hypotheses, original of the Thesis, (Co-creation Interaction, Perceived Value Interaction, and Satisfaction Interaction) were supported in both contexts, revealing the importance of Interaction for Loyalty as well as Perceived Value, Satisfaction and Brand Image. In DL, only two hypotheses were not supported (Co-creation of Perceived Value, Co-creation of Value Satisfaction, in direct and mediation relations) contrary to the Responsible Service Logic and Transactional Distance and Learning Theories. Then, given the recent permission of MEC to up to 40% of DL in hours Classroom Teaching classes (which reduces Interaction), it raises concern and demands more managerial reflection and research. In the Rival Model, the Brand Image, which, although its direct relations have been supported in the Main Model, that construct mediated the relationships Satisfaction Loyalty and Perceived Value Loyalty. From the multi-group analysis, 15 relations showed differences, in 10, the coefficients were more significant for DL students than for the student of Classroom Teaching. From the 10 significant relationships in DL, 8 involve Interaction, indicating its importance to the DL???s student. The Dissertation can serve academically and managerially to public and private spheres. In academy, the background to DL Loyalty is a frontier to be expanded. Managerially, a model of student loyalty centered on interaction can guide the efforts of educational institutions. Finally, the regulatory bodies of Higher Education receive supports to their functions of planning, executing and controlling DL towards excellence.